Phytochemical Profiles and Antioxidant Activity of Grasses Used in South African Traditional Medicine - Gebashe, Fikisiwe; Aremu, Adeyemi O; Gruz, Jiri; Finnie, Jeffrey F; Van Staden, Johannes (Plants (Basel, Switzerland), 2020)
Grasses are a valuable group of monocotyledonous plants, used as nourishing foods and as remedies against diseases for both humans and livestock. Phytochemical profiles of 13 medicinal grasses were quantified, using spectrophotometric methods and ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS), while the antioxidant activity was done using DPPH and ferric-reducing-power assays. The phytochemical analysis included the total soluble phenolic content, flavonoids, proanthocyanidins, iridoids and phenolic acids. Among the 13 grasses, the root methanolic extracts of Cymbopogon spp., Cymbopogon nardus and Cenchrus ciliaris contained the highest concentrations of total soluble phenolics (27-31 mg GAE/g DW) and flavonoids (4-13 mg CE/g DW). Condensed tannins and total iridoid content were highest (2.3 mg CCE/g DW and 3.2 mg HE/g DW, respectively) in Cymbopogon nardus. The most common phenolic compounds in the grass species included ρ-coumaric, ferulic, salicylic and vanillic acids. In the DPPH radical scavenging assay, the EC50 values ranged from 0.02 to 0.11 mg/mL for the different grasses. The best EC50 activity (lowest) was exhibited by Cymbopogon nardus roots (0.02 mg/mL) and inflorescences (0.04 mg/mL), Cymbopogon spp. roots (0.04 mg/mL) and Vetiveria zizanioides leaves (0.06 mg/mL). The highest ferric-reducing power was detected in the whole plant extract of Cynodon dactylon (0.085 ± 0.45; r2 = 0.898). The observed antioxidant activity in the various parts of the grasses may be due to their rich pool of phytochemicals. Thus, some of these grasses provide a source of natural antioxidants and phytochemicals that can be explored for their therapeutic purposes.
Keywords: medicinal plants; phenolic acids; secondary metabolites; flavonoids; UHPLC; Poaceae